Evaluation of a Computer Application for Retrospective Detection of Vitamin K Antagonist Treatment Imbalance. Issue 2 (June 2018) - Ferret, Laurie; Luyckx, Michel; Ficheur, Grégoire; Chazard, Emmanuel; Beuscart, Régis
Abstract : Objective: Management of vitamin K antagonists (VKAs) is difficult, and overdoses can have dramatic hemorrhagic consequences. The adverse drug event (ADE) scorecards is a tool intended for the detection and description of adverse drug reaction/ADE developed during a European computerized medical data processing project. It is used in a quality assurance process. Our objective was to evaluate the performance of the ADE scorecards in the detection of the contributing factors for VKA overdoses, among the cases where a VKA overdose is observed. Methods: Twenty-eight rules allow the detection of VKA treatment overdose related to drug or a clinical situation. They were applied on 14, 748 electronic medical records from a community hospital. Among 582 records including a VKA prescription, 59 cases of VKA overdoses (international normalized ratio ≥ 5) during the hospital stay have been identified. The ADE scorecards detected 49 of them. We evaluated the positive predictive value and sensitivity of these rules, by an expert review of the cases. Results: The expert review confirmed the contribution of a detected risk factor to the VKA overdose in 11 cases. Therefore, the precision of the rules is 22.4%. The sensitivity is 84.6%. The risk factors were mainly infection and amiodarone introduction. The 4 cases of clinical injury related to a drug were properly designated by the rules. Conclusions: Our study shows the great potential of the ADE scorecards for detecting cofactors of VKA overdoses and gives an argument to include complex rules in the knowledge bases used for the detection and identification of ADEs in large medical databases.